2011
DOI: 10.2174/156652411798062386
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Facets of COMT: From a Plausible Predictive Marker to a Potential Drug Target for Schizophrenia

Abstract: Dopaminergic system in the prefrontal cortex (PFC) is known to regulate the cognitive functions. Catechol-O-methyl transferase (COMT), one of the major modulators of prefrontal dopamine function, has emerged as an important determinant of schizophrenia associated cognitive dysfunction and response to antipsychotics. A common Val->Met polymorphism (rs4680) in the COMT gene, associated with increased prefrontal dopamine catabolism, impairs prefrontal cognition and might increase risk for schizophrenia. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 101 publications
0
13
0
1
Order By: Relevance
“…COMT is involved in the degradation of dopamine and is important in the regulation of dopaminergic prefrontal cortex dependent cognitive disturbances in schizophrenia (Gupta et al, 2011). The authors reported significant effects of COMT deletion to enhance WM performance in male, but not female, COMT -/-mice (Babovic et al, 2008) that could be related to higher prefrontal dopamine levels ( Table 2).…”
Section: Working and Short-term Memorymentioning
confidence: 99%
“…COMT is involved in the degradation of dopamine and is important in the regulation of dopaminergic prefrontal cortex dependent cognitive disturbances in schizophrenia (Gupta et al, 2011). The authors reported significant effects of COMT deletion to enhance WM performance in male, but not female, COMT -/-mice (Babovic et al, 2008) that could be related to higher prefrontal dopamine levels ( Table 2).…”
Section: Working and Short-term Memorymentioning
confidence: 99%
“…That the nicotine‐induced electrocortical changes were evident in individuals with the COMT Met allele infers that the acute, nicotine‐modulated spontaneous oscillations reflect tonic cortical dopamine level and its potential functional role in cognitive tasks. These spectral EEG findings were observed with respect to α oscillatory activity, which is associated with cognitive processes and therefore may be of relevance to people diagnosed with schizophrenia – a disorder invariably linked with COMT polymorphism (Gupta et al ; Lewandowski ; Sagud et al ; Williams et al ), and is also associated with excessive smoking (Winterer ), aberrant dopamine neurotransmission (Brisch et al ), abnormalities in α rhythms (Knott et al ; Narayanan et al ; Venables et al ; Wix‐Ramos et al ), fMRI– (Whitfield‐Gabrieli et al ) and electrophysiologic–DMN (Kim et al ) and cognition (Nuechterlein et al ), with the latter being shown to improve both with smoking and nicotine administration (D'Souza & Markou ). Schizophrenia patients have shown increases in α 2 with the smoking of a single cigarette (Knott et al ), but the role of COMT in these oscillatory changes is not yet known and the cognitive changes accompanying these cortical rhythms require addressing.…”
Section: Resultsmentioning
confidence: 87%
“…The antipsychotic drug aripiprazol is a partial D2 agonist and improves cognitive functions, but impairs motor activities [19]. Dopamine hyperactivity is associated with polymorphisms of the catechol-O-methyl transferase gene and reduced dopamine degradation leads to dopamine hyperactivity and cognitive impairments [20]. The action of the enantiomers (-)-OSU-6,162 and (+)-OSU-6,162 has been reported, which are partial agonists at both D2 and 5-HT2A receptors.…”
Section: Dopaminementioning
confidence: 99%